Teachers’ Beliefs Versus Learners’ Beliefs In Grammar Teaching: Harmonizing Teaching and Learning for Adult Learners’ Improved Proficiency In English - Ahmad, Iftikhar; Hussain, Muhammad Sabboor; Noor Raha, Mohd Radzuan (Australian International Academic Centre PTY. LTD., 2017)

(untitled)
The study tends to explore the possible reforms to raise the proficiency level of the adult English as Foreign Language (EFL) learners. With this end in view, it investigates non-native EFL teachers’ beliefs in relation to adult learners’ beliefs in teaching grammar to university students in the Saudi Arabian EFL context. It finds out the harmony and disharmony between the teachers at the giving end and the taught at the receiving end to create a culture of awareness and to build a better teaching learning environment. The study tries to fill the existing research gap as no previous research has tried to find out the solution to the problem from this angle. The main data collection tools are two five-point Likert-scale questionnaires, administered to 70 non-native EFL teachers and their 80 adult students. Teachers and learners have been selected based on stratified random sampling. Quantitative data have been analyzed using the statistical package for social sciences (SPSS). The major finding of the study are that there is discrepancy in the grammar teaching beliefs of the EFL teachers and the taught and there is a communication gap between them which result into low English proficiency. level of the EFL adult learners. Eventually, pedagogical implications of the lack of harmony between the teachers’ teaching creeds and the learners’ learning demands/expectations are provided for effective grammar teaching and better EFL classroom environment. The study recommends a better communicative harmony in both the stakeholders to bring reforms in adult education in EFL context